Social Media Trends in Learning Islamic Religious Education in the Era of Society 5.0 - Fajri, Fahmi Nur; Wibowo, Heru (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
The urgency of transforming Islamic Religious Education (PAI) learning in the digital era is increasing along with the widespread use of social media as an alternative learning space that is more interactive, flexible, and contextual. This study aims to map the trends and direction of the development of scientific studies related to the use of social media in PAI learning with a bibliometric approach. Data were taken from the Scopus database for the period 2015–2025 with 768 articles selected through a screening process based on the PRISMA protocol. The analysis was performed using R software with the Bibliometrix library and the Biblioshiny visual interface. The results show a significant surge in publications since 2020, dominated by social sciences and humanities disciplines, with the largest contributions coming from the United States and Indonesia. The main topics that emerged included digital da'wah, media-based Islamic education, and the religious identity of the younger generation. The novelty of this study lies in the presentation of a conceptual framework based on bibliometric data that integrates the mediatization of religion and digital literacy as an analytical lens. This research makes an important contribution in formulating the direction of digital Islamic education policies and opens up opportunities for cross-disciplinary collaboration for the development of an adaptive and transformative PAI curriculum in the Society 5.0 era.